Fetal Inferior Vena Cava Thrombosis Associated With Non-Immune Hydrops Fetalis and Maternal Mirror Syndrome - Foxworthy, Kimberly M; Lamb, Eneka; Weymon, Alexandria; Roloff, Emily; Garcia De Paredes, Jessica; Frost, Jamie; Romero, Vivian C (Curēus (Palo Alto, CA), 2023)
Prenatal assessment of the inferior vena cava (IVC) should be considered in pregnancies with atypical presentations of fetal ascites and placentomegaly. We examine a case of a 25-year-old gravida 2 para 1 type 1 diabetic female at 29 and 4/7 weeks' gestation. Ultrasound (US) showed fetal ascites and placentomegaly with increased middle cerebral artery peak systolic velocity (MCA-PSV) suspicious of fetal anemia. Cordocentesis with intrauterine transfusion briefly resolved the fetal ascites, though the mother developed pulmonary edema and pleural effusion, suggestive of mirror syndrome. On US, fetal ascites returned and progressed to non-immune hydrops fetalis, prompting delivery. Neonatal US revealed a heterogenous and calcified thrombus within the IVC.